The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2196/40326
|View full text |Cite
|
Sign up to set email alerts
|

Improved Glycemia and Quality of Life Among Loop Users: Analysis of Real-world Data From a Single Center

Abstract: Background Despite do-it-yourself automated insulin delivery being an unapproved method of insulin delivery, an increasing number of people with type 1 diabetes (T1D) worldwide are choosing to use Loop, a do-it-yourself automated insulin delivery system. Objective In this study, we aimed to assess glycemic outcomes, safety, and the perceived impact on quality of life (QOL) in a local Edmonton cohort of known Loop users. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Several studies from self-reported data have preliminarily observed the efficacy and safety of DIY APS among patients with T1DM. [18][19][20][21][22][23][24][25] However, these studies with small sample sizes and highly selective, observational, single-arm and before-after controlled designs make it difficult to reach conclusions. High-quality evidence is needed to explore DIY APS outcomes.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Several studies from self-reported data have preliminarily observed the efficacy and safety of DIY APS among patients with T1DM. [18][19][20][21][22][23][24][25] However, these studies with small sample sizes and highly selective, observational, single-arm and before-after controlled designs make it difficult to reach conclusions. High-quality evidence is needed to explore DIY APS outcomes.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%